Sejarah Baileo Baihata Kapalatu Dan Fungsinya Dalam Kehidupan Masyarakat Adat Negeri Ameth di Pulau Nusalaut Kabupaten Maluku Tengah - Balsala, Sontaria; Pattiasina, Johan; Ima, Wa (Program Studi Pendidikan Sejarah, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pattimura, 2024)
The Baileo located in Negeri Ameth is called Baihata Kapalatu, and the village's original name (teon) is Samasuru Amalatu. Etymologically, Samasuru Amalatu means a village led by a latu (king) established due to a command. Research shows that there are three entrances to this Baileo, each related to the roles of three villages: Ameth, Nalahia, and Akoon. In the past, these three villages were part of Ina Huhu, with Ameth serving as Ina Huhu's head and Titawaai as Ina Haha's head. According to some traditional elders, the southern entrance is for the village of Akoon, the western entrance is for Ameth, and the northern entrance is for Nalahia.Before the construction of the Baileo in Negeri Ameth, all meetings concerning decision-making for issues related to Ameth were held in the old village in the mountains, where the community had yet to establish permanent residences. The people of Ameth believed they needed to move down to the coast and build a settlement. Using a tool called a lobe, which was thrown downwards, they decided where the lobe landed. A sacred stone was placed at this spot, and next to it, the Baileo of Negeri Ameth, named Baihata Kapalatu, was built. It is known that Baihata Kapalatu was originally the Baileo of Ina Huhu, belonging to Ameth as the king and Akoon and Nalahia as chiefs. Thus, all matters concerning these three villages were once handled within this Baileo. However, over time, the Baileo ceased to serve the towns of Akoon and Nalahia as they each built their own Baileo. Consequently, matters related to these two villages are no longer conducted in Baihata Kapalatu but are now handled within their respective Baileo. The Baileo in Negeri Ameth plays a vital role in conducting governmental ceremonies and traditional rituals within the village. The people of Ameth also believe that the Baileo is a sacred place that must be preserved and respected, as it is an integral part of the culture of the Maluku people, particularly the indigenous community of Negeri Ameth.